The Analysis of Confucian Followers’ Understanding of Gods in Confucianism, Buddhism, and Taoism in Bangka Island - Indonesia - Sugiato Lim (Humaniora, 2013)
Indonesia is a multi-ethnic, multi-culture, and multi-faith country. This piece of land combines a lot of ethnic elements into one. For example, Confucianism in Indonesia is combination of Confucianism, Buddhism, and Taoism characteristic in many ways. Aim of this paper is to find out the features of Confucianism as a religion or a belief for its followers in Bangka. In addition, this paper also focuses on finding out the followers view towards their Gods in their perspectives. In this article, classification of Gods in Confucianism, Buddhism, and Taoism is presented based on direct social observation. In this paper, analysis of Confucian followers understanding towards Gods in Confucianism, Buddhism, and Taoism in Bangka Island Indonesia is presented respectively. In conclusion, characteristics of these three religions have blended perfectly and there is no more distinction in Confucius, Buddhist or Taoism Gods in Confucian followers’ community in Bangka Island.